2007
DOI: 10.1111/j.1365-2036.2007.03389.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal‐systemic shunting in patients with fibrosis or cirrhosis due to chronic hepatitis C: the minimal model for measuring cholate clearances and shunt

Abstract: SUMMARY BackgroundMeasurement of portal inflow and portal-systemic shunt using cholate clearances could be useful in monitoring patients with liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Other tests measure hepatic circulation using test compounds with flowdependent, high firstpass hepatic extraction such as galactose (galactose elimination capacity 115 and cholate clearances and shunt 116 . Although attractive candidates to assess response to a treatment, the clin ical validity of these parameters has yet to be estab lished and thus the clinical importance of any change remains uncertain.…”
Section: Blood Measures Of Liver Regenerationmentioning
confidence: 99%
“…Other tests measure hepatic circulation using test compounds with flowdependent, high firstpass hepatic extraction such as galactose (galactose elimination capacity 115 and cholate clearances and shunt 116 . Although attractive candidates to assess response to a treatment, the clin ical validity of these parameters has yet to be estab lished and thus the clinical importance of any change remains uncertain.…”
Section: Blood Measures Of Liver Regenerationmentioning
confidence: 99%
“…Everson et al [50 ] compared different 'quantitative' liver function tests in the frame of an antiviral hepatitis C treatment (HALT) study. The best test proved to be a 'dual isotope tracer' approach, in which different isotopic variants of the bile acid cholate were given orally and intravenously [51]. Using plasma enrichment values of both tracers, flow rates were quantified for the portovenous perfusion shunt, for the entero-hepatic cycling of bile acids and their excretion.…”
Section: Monitoringmentioning
confidence: 99%
“…To keep the tests as simple and as noninvasive as possible, measurements of the plasma tracer enrichment values or a parallel infusion of different tracer compounds, which all would provide additional, useful information, were abandoned. The power of more extended tracer studies is outlined by Beylot [65] and was demonstrated with the 'cholate-liver function test' [51]. Another extended tracer approach was used to assess amino acid absorption and metabolism [66,67].…”
Section: Joint Determination Of Gastric Emptying and Liver Functionmentioning
confidence: 99%
“…Cholates have been safely administered both orally and intravenously 1,9,23,24 . In the dual test, [2,2,4,4-D]cholate (D4-cholate)is administered orally and, [24- 13 C]cholate (13C-cholate) is administered intravenously, simultaneously.…”
Section: Dual Cholate Testmentioning
confidence: 99%